Feminine physiology in the drama "Krzywicka/Blood" by Julia Holewińska - Tarasińska, Joanna (To Tell the History: Polish Contemporary Dramaturgy after 2006, 2023)
The female body in Polish culture is still perceived ambiguously. On the one hand, we are dealing with the eroticization or sexualization of female images. A woman is to be an attractive object of desire and at the same time meet a number of requirements regarding her appearance, character and lifestyle. On the other hand, you can hear that you only talk about what is in some way comfortable and aesthetic. It is related to centuries of narrating from a male point of view and perceiving reality through the prism of features or spheres of life commonly associated with the world of men.A breakthrough of a kind in Polish contemporary drama is Julia Holewińska's "Krzywicka/ Krew". Based on the biography of Irena Krzywicka, a writer and promoter of conscious motherhood, contraception and sexual education, the author created a female polyphony that reveals to everyone the female intimacy associated with various types of blood or body transformations. The playwright does not tell the story of Krzywicka directly - the main character can be recognized in the dilemmas of the female characters and the events of their lives. Thus, the work is a strong part of the herstoric trend. It is the perspective of women that is at the fore here - their role in society, perception of their own body, their own sexuality, and a sense of worth. They themselves talk about gender-related issues.Holewińska's drama and its productions (Modrzejewska Theater in Legnica and Horzyca Theater in Toruń) are a commentary on an important social problem - tabooing, among others, physiological processes taking place in the body of a woman, and at the same time give voice to women so that they can talk about themselves without men as intermediaries. That is why it is important to list "Krzywicka/ Krew" among contemporary dramas.